(untitled) (Journal of Health Sciences, 2013)
Introduction: New, up-to-date approaches to professionalism presuppose the formation of a nursing team in such a way that relationships are not based on classical hierarchical relationships between superiors and subordinates but on relationships of interdependence and acknowledgment of the role the individual plays in the team. The objective of this article is to present the competences required by nurses in top organizational leadership positions from two viewpoints: as seen by nurses in top leadership positions and as seen by nurses in subordinate positions.Methods: A descriptive research method using a questionnaire as the measuring instrument was used. The questionnaire was based on the competence model of leadership in public administration in Slovenia and was tested on various professional groups.Results: Statistically signifi cant differences were observed with regard to the majority of competences between nurses in top leadership positions and nurses in non-leadership positions. Therefore, the views regarding what competences nurses in leadership positions should have substantially differed within theprofessional group.Conclusions: The fi rst conclusion is therefore that education on leadership on both the theoretical and practical levels must be introduced into undergraduate study programmes of health colleges. With the help of factor analysis we formed fi ve subgroups within the professional group of nurses: three subgroups within the group of nurses in leadership positions and two subgroups within the group of nurses in nonleadershippositions. A special education programme should be prepared for each of these subgroups.